Indicators of intracardiac haemodynamics in patients with chronic coronary syndrome with concomitant coronavirus disease (COVID-19) - Netiazhenko , Vasil; Mostovyi , Serhii; Potashov , Serhii; Safonova , Olga (The Ukrainian Scientific Medical Youth Journal, 2024)
the nature of cardiovascular damage caused by SARS-CoV-2 coronavirus infection due to acute severe respiratory distress syndrome is associated with high mortality. However, the pathophysiological impact of COVID-19 (C19) on intracardiac haemodynamics remains unknown. The aim of our study was to evaluate intracardiac haemodynamics in patients with chronic coronary syndrome (CCS) in combination with coronavirus disease (COVID-19). The prospective study included: 30 patients with CAD with a negative PCR test for COVID-19 (1Agroup), 38 patients with CAD with a positive PCR test for COVID-19 (1Bgroup), of whom 12 were diagnosed with an increase in the level of troponin I (1B/T+), 26 patients had a normal level of troponin I (1B/T-). As a comparison, 30 patients with COVID-19 with PCR(+), without signs of CAD - group 2, as well as 30 healthy volunteers without signs of CAD and with negative PCR were studied. Clinical and laboratory data, treatment, and intracardiac haemodynamics were assessed by echocardiography in all groups. The left ventricular myocardial mass index, left ventricular end-diastolic volume, right ventricular size, and pulmonary artery systolic pressure were highest in the group of CAD with COVID-19 with a positive troponin test (1B/T+), compared with the (1B/T-) group, also in the (1B/T+) group, the ejection fraction and total longitudinal strain by speckle tracking were lower than in the (1B/T-) group. When compared with group 1A, LVEF was lower in the (1B/T+) group, and STla was higher in the (1B/T+) group. When comparing the indicators of group 1A and (1B/T-), a similar pattern of changes in intracardiac haemodynamics was noted: LV myocardial mass index, right ventricular diameter, systolic pressure in the pulmonary artery were higher, while longitudinal strain was slightly lower in (1B/T-) than in group 1A. When comparing the echocardiography parameters of patients in the (1B/T+) subgroup with group 2, larger left ventricular end-diastolic volume, left atrium, left ventricular myocardial mass index were found in (1B/T+), but the ejection fraction was lower in (1B/T+), while the right ventricular size and pulmonary artery systolic pressure were slightly higher than in group 2. In the subgroup (1B/T-), the nature of the changes was similar, but the size of the RV and PASP did not differ from those in group 2. The echocardiographic parameters of group 1A differed from those of group 2 by higher values of LVEF, LVEDV, LVMMS and lower EF, but the size of the RV and PASP were larger in patients with COVID-19. Cardiac damage associated with SARS-CoV-2 in patients with concomitant CAD has an effect on the myocardium, which is manifested in an increase in left ventricular EF due to increased preload, at the expense of a decrease in global strain and systolic function of the LV myocardium, due to the direct cytotoxic effect of SARS-CoV-2 on the one hand, and destabilisation of existing atherosclerotic plaques, as well as hypoxia and worsening of endothelial dysfunction on the other. An increase in the size of the right ventricle is associated with an increase in peripheral vascular resistance in the small circle as a consequence of increased systolic pressure in the pulmonary artery in covidassociated pneumonia. The impact of SARS-CoV-2 infection on the heart is associated with cardiovascular risk factors and the severity of the inflammatory process.